The Theory of Intellectual Supra-abstractedness of the Soul in the Avicennan Philosophy - Aynullāh Khādimī; Sayyid Alī Razizādeh (حکمت اسرا, 2011)
The theory of intellectual supra-abstractedness of the soul is in fact abstractedness from quiddity, expansion of the existential capacity of the soul, and its non-stop progress upward through the arch of ascent and proximity to God. In addition to the stage of abstractedness, the human soul holds an incessant and supra-abstractedness level; a level at which man becomes free from his essence and identity, and ego is removed from him to such an extent that he would have no individuality and definite standing to be referred to. It was Plotinus who first introduced it and then Suhrawardī and Mullā Ñadrā discussed it. However, examination of the role of Aristotle in the theory of Ibn Sīnā concerning the supra-intellectuality suggests that the latter neither seems to have spoken of the supra-abstractedness of the soul nor of its abstractedness from the quiddity. In his treatise al-nafs, Ibn Sīnā believes in the limitedness of faculties of the soul in a specific end (on the plane of the intellect) as well as the limitedness of the theoretical intellect (on the plane of the acquired intellect, al-aql al-mustafād). Likewise, influenced by Aristotle, he maintains that substantiality of the soul causes it to be caught in the grip of the quiddity (genus, differntia, definition and composition) and finally fallen under a given category. This idea is in disagreement with the soul being beyond category in this level. The present article claims that although no conclusive, definitive proof can be offered concerning Avicenna’s belief in the theory of intellectual supra-abstractedness of the soul; yet perhaps one can find limited evidence in his works indicating the rejection of this theory.